Improved mRNA-based RSV vaccine with PreF forming enveloped virus-like particles - Pengdi Chai; Yi Shi; Xiaoyan Li; Mengyao Yang; Xiafei Liu; Mei Liu; Junjie Yu; Xiaoxuan Yin; Dongwei Li; Ke Li; Xiangyu Kong; Qin Zhang; et al. (npj Vaccines)
Abstract Respiratory syncytial virus (RSV) causes severe respiratory disease in infants and the elderly. However, natural infection fails to induce durable immune protection, and existing mRNA vaccines for older adults exhibit limited long-term efficacy. We developed an antigen engineering strategy inserting ESCRT/ALIX-binding region (EABR) into truncated RSV prefusion F (PreF) cytoplasmic tails to form enveloped virus-like particles (eVLPs). In murine models, PreF-EABR mRNA vaccines elicited higher, more persistent neutralizing antibodies than conventional PreF mRNA, correlating with enhanced germinal center B cell and memory B cell responses. A lower dose of PreF-EABR mRNA (1 μg) suppressed viral load and pathology comparable to higher-dose PreF mRNA (2.5 μg). Transcriptomic analysis showed PreF-EABR mRNA activated toll-like receptor and chemokine signaling pathways, enhancing antibody longevity via platelet-associated signatures. This study explores the development and possible mechanism of long-lasting RSV mRNA vaccines by eVLPs technology, which also suggest its potential application in other vaccines.